Effects of 4 h preexercise carbohydrate feedings on cycling performance - Sherman, W. M.; Brodowicz, G.; Wright, D. A.; Allen, W. K.; Simonsen, J.; Dernbach, A. (Medicine & Science in Sports & Exercise, 1989)
This study determined the effects of consuming three different amounts of liquid carbohydrate 4 h before exercise on the metabolic responses during exercise and on exercise performance. Four hours before exercise subjects consumed either 45 (L) or 156 (M) g of carbohydrate in isocaloric feedings and either 0 (P) or 312 (H) g of carbohydrate. Interval cycling was undertaken for 95 min, followed by a performance trial. Blood glucose had reached basal 1 h after all feedings; blood insulin had reached basal 3 h after ingestion of P, L, and M but was still 84% higher for H at the start of exercise. During exercise insulin averaged 48% higher for H than P. Blood glucose decreased 16% during exercise for P, L, and M, whereas for H there was a transient drop the first 15 min of exercise, after which glucose increased and remained constant throughout exercise. More carbohydrate oxidation occurred during exercise for H vs P, whereas results were similar for L and M. Ingestion of H improved performance by 15% as compared with P, whereas performance was similar for L and M. These results indicate that, despite elevated insulin at the start of and during exercise, consumption of 312 g of carbohydrate 4 h before moderately intense prolonged exercise can improve performance, perhaps via an enhancement of carbohydrate oxidation.